PENGARUH CAR, NPF, FDR, NPM DAN PEMBIAYAAN MUDHARABAH TERHADAP PROFITABILITAS BANK UMUM SYARIAH (Studi kasus pada Bank Umum Syariah yang terdaftar di Indonesia periode 2015-2019) - Ega Mayang Usmayanti (Jurnal Ilmiah Penelitian Mahasiswa, 2022)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), NonPerforming Financing (NPF), Financing to Deposit Ratio (FDR), Net ProfitMargin (NPM) and Mudharabah Financing on Profitability at Indonesian IslamicCommercial Banks as proxied by Return On Assets. (ROA). This research is aquantitative research. The population of the data is Sharia Commercial Banksregistered in Indonesia for the 2015-2019 period. Sampling using purposivesampling method and obtained 65 samples. This study uses secondary data fromfinancial statements. Data analysis using Multiple Linear Regression Analysismethod. Based on the tests that have been carried out, it can be said that theCapital Adequacy Ratio (CAR) has a positive and insignificant effect onProfitability, Non-Performing Financing (NPF) has a significant negative effecton Profitability, Financing to Deposit Ratio (FDR) has an insignificant positiveeffect on Profitability, Net Profit Margin (NPM) has no significant positive effecton Profitability, and Mudharabah Financing has no significant negative effect onProfitability